2021
DOI: 10.1111/jcmm.16706
|View full text |Cite
|
Sign up to set email alerts
|

PLAC8 promotes adriamycin resistance via blocking autophagy in breast cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Reports of PLAC8 cellular localization vary depending on cell type, from cytosolic, to lysosomal ( 23 , 24 ), to the apical domain of differentiated human intestinal epithelium ( 25 ) and/or the inner leaflet of the plasma membrane ( 24 ), although cell surface localization has not been demonstrated. PLAC8 is reported to be involved in multiple complex cellular pathways, including autophagy ( 24 27 ), epithelial-mesenchymal transition (EMT), cell motility, innate immune functions ( 22 , 28 ), mitochondrial metabolism, and DNA repair ( 29 ). In particular, autophagy is known to be important in CoV infections.…”
Section: Resultsmentioning
confidence: 99%
“…Reports of PLAC8 cellular localization vary depending on cell type, from cytosolic, to lysosomal ( 23 , 24 ), to the apical domain of differentiated human intestinal epithelium ( 25 ) and/or the inner leaflet of the plasma membrane ( 24 ), although cell surface localization has not been demonstrated. PLAC8 is reported to be involved in multiple complex cellular pathways, including autophagy ( 24 27 ), epithelial-mesenchymal transition (EMT), cell motility, innate immune functions ( 22 , 28 ), mitochondrial metabolism, and DNA repair ( 29 ). In particular, autophagy is known to be important in CoV infections.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapy can inhibit autophagy by regulating microRNA mediated downstream signaling pathways, and promote tumor resistance, such as microRNA-199a-5p 51 and miR-519a. 52 Similar phenomenon was also observed in resistance to cisplatin, 5-fluorouracil and doxorubicin, by activating PI3K-Akt-mTOR signaling to inhibit autophagy, [53][54][55] suggesting that inhibition of autophagy is a key factor.…”
Section: Autophagy Inhibition Promotes Conventional Treatment Resistancementioning
confidence: 57%
“…Our previous research suggested that PLAC8 can promote breast cancer cell growth and participate in the process of tamoxifen and adriamycin resistance. [8][9][10] As we mentioned in our review, 11 PLAC8 also plays an important role in various cancers and is involved in tumor progression, including in programmed cell death,…”
Section: Introductionmentioning
confidence: 90%